CARDIOVASCULAR DEVICES WITH MULTIFUNCTIONAL HYDROGEL COATINGS: FIGHTING INFECTION AND THROMBOSIS AT THE SAME TIME - Missfer Saud Alajmi, Mohammed Mubarak Alabdulhadi, Mohammed Ali Alali,Thamer Nasser Aldhayan, Thamer Abdulaziz Alamer, Fahad Mohammed Al Thafir, Sultan Ghusayn Aldawsari, Mohammed Abdullah Khuraizan Alskhabrah,; Zakaria Mohammed Al Muhaymid, Hamad Muflih Alshaghathirah, Abdullah Ali Qahtani, Nasser Saeed Mobark Alwuhayyid, Meshal Rashed Abdullah Aljomah, Husam Abdullah Alotaibi (Chelonian Research Foundation, 2022)
Thromboembolic and infectious consequences resulting from the use of cardiovascular devices continue to be prevalent and cause a considerable amount of morbidity and mortality. Up until now, there hasn't been a plan that successfully tackles both problems at once. There are many surface modification techniques that have been suggested, such as liquid-impregnated surfaces, heparin- and silver-impregnated surfaces, however they all have drawbacks and restrictions. Here, it is demonstrated that bacterial adhesion to medical-grade tubing is reduced by 95% by including an ultrathin and mechanically strong hydrogel layer. Additionally, it is shown that the hydrogel layer significantly lowers blood clot formation and adherence to the tubing without compromising the blood's inherent clotting capabilities using a mix of in vitro and in vivo studies. In an in vivo porcine model, the adherence of clots to the tubing walls is reduced by over 90% (in vitro model), leading to an approximately 60% increase in the device occlusion time (time before closure due to clot formation). Because of these passive coating's advantageous properties, it is a promising surface material candidate for medical devices that interface with blood diseases, such as cancer, end-stage renal disease, cardiovascular disease, and the care of critically ill patients in the intensive care unit (ICU). Keywords: Hydrogel coatings, blood-contacting devices, thrombosis, bacterial adhesion, cardiovascular implants.